Resource management for librarians - Ologbonsaiye, Richard I. (Lagos, Nigeria : Concept Publications Ltd., 1994)
This stresses the importance of applying management tools and principle in Library administrations.
Includes bibliographical references and index.
kjo 18/01/2019
Loans
Keywords: Library Management